IMPLEMENTASI PENGELOLAAN PRIORITAS PENGGUNAAN DANA DESA DI DESA LABAN KECAMATAN MOJOLABAN KEBUPATEN SUKOHARJO - Mardikaningrum, Kusuma Prastiwi; Achmad, Achmad (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2018)
This study describes and examines the problems of: firstly how the implementation of usage management priority of the village funds, especially in Laban Village the Sub-district of Mojolaban of Sukoharjo Regency in 2017, secondly what are the obstacles that occur in the process of implementing the use of Village. This study is the type of empirical legal research. Sources of data in this study using primary data sources, and secondary data sources. The techniques of data collections are from interview and observation techniques, from data that has been collected, then will be analyzed.The results of this research indicate that implementation of usage management priority of the village fund in 2017 is focused on the development of basic infrastructure, such as road construction, culverts, ducts, and dams. The budget of the Village Fund in 2017 had not been used for community empowerment. Obstacles that occur in the usage of Village Funds such as: the level of community participation in the planning stage is less than maximum, the liquefaction stage is delayed because arrangment of the APBDes is too long, the implementation stage is not accordance with the Village Ministerial Regulation Number 22 Year 2016 about implementation of usage management priority of the village fund in 2017, lack of community to oversee the usage of the Village Fund, and inadequate human resources in making accountability reports.